Lesson of gymnastic from the point of view the collegeof sport –education –university of BaghdadFor the year 2007 -2008 - Mohammed, Sundus; Hussein, Saleem; Hamid, Nabhan; Habeeb, Hussein (Journal of Physical Education, 2009)
The research aim to learn (know)aboutch the place of strong and weak in the lesson of gymnastics through out the question ofabout that –the assumptionof the research is increase the equipment and motion which demands eah equipment leads to onfuse the student and prevent him motion in good manner and not enough time for the lesson of gymnastics the research performed in the college of sport-education .university of Baghdad and reach to desire the students in learning agood motions concerned with the lesson of gymnastics after the lessons and show the motion by the teacher received satisfactions in addition to the use of analytical ,explanatory and demanded the necessity to provide dramatic films and increase the nembers of teachers who spicailized in gymnastcs art درس الجمناستك من وجهة نظر طلبة كلية التربية الرياضية – جامعة بغداد للعام الدراسي 2007/2008